Sleep quality, sleep hygiene awareness, and chronotype in nursing shift workers - Nirav Bhupendrabhai Chanpa; Deepak Sachidanand Tiwari; Vishal Kanhiyalal Patel; Dhruv Shaileshbhai Patel (Annals of Indian Psychiatry, 2022)
Background: Shift workers have various physical and psychological adverse effects due to their work schedule. Some of them are reporting poor sleep quality. Our study aimed to measure sleep quality and its relation with sleep hygiene awareness and chronotype in nursing shift duty workers. Materials and Methods: A cross-sectional survey had been carried out in nursing shift duty workers working at a tertiary care center. A total of 300 participants were recruited through convenient sampling. After taking ethical approval, consented participants were made to fill the pro forma which contained basic demographic details and scales such as Pittsburgh Sleep Quality Index, Sleep Belief Scale, and Composite Scale of Morningness. Data were entered and analyzed using trial version of SPSS. Results: Around 40% of the participants had poor sleep quality. Sleep quality had been statistically significantly associated with sleep hygiene awareness and chronotype of shift workers. Sleep quality had also been associated with needle stick injury and usage of sleeping pills. Conclusion: shift workers with poor sleep quality were more likely to have lower sleep hygiene awareness and evening type of chronotype. Elder shift workers had good sleep quality, better sleep hygiene awareness, and better morning-type chronotype as compared with younger shift workers.